Asuhan Keperawatan Jiwa pada Pasien dengan Halusinasi Pendengaran Di Wisma Nuri Rumah Sakit Jiwa Prof Dr HB Saanin Padang - Wella Wulansari; Ramaita Ramaita; Dwi Happy Anggia Sari; Vivi Yuderna (CV. ITTC INDONESIA, 2026)
Hallucinations are a condition in which a person loses the ability to distinguish between internal and external stimuli, resulting in the perception of the environment without any real objects or stimuli. This condition is often found in patients with mental disorders and can affect social functioning and quality of life. Based on medical records at Prof. DR. HB Sa’anin Mental Hospital, Padang, the most common nursing problem in the past three years has been hallucinations, with 17,591 patients. The purpose of this case study is to apply psychiatric nursing care to patients with auditory hallucinations at Prof. DR. HB Saanin Mental Hospital. HB Saanin Padang. The method used in this scientific paper is a case study with a nursing process approach, including assessment, diagnosis, planning, implementation, and evaluation. The assessment results indicated that the patient experienced signs and symptoms of hallucinations, including hearing whispers. The primary nursing diagnosis was hallucinations, with a co-diagnosis of self-care deficit (SDC). After nursing care, the patient was able to address self-care issues and control hallucinations independently through the implementation of Implementation Strategies (SP): SP 1: practicing reprimands, SP 2: taking medication regularly, SP 3: having conversations, and SP 4: carrying out scheduled daily activities. These results indicate that the implementation of implementation strategies is effective in helping the patient control hallucinations and improving self-care skills. It is hoped that through this research, everyone can understand the importance of psychiatric nursing care, thereby increasing awareness in maintaining and preserving mental health, and adopting behaviors that support optimal mental well-being in daily life.